(untitled) (American Journal of Interdisciplinary Research and Development, 2024)
The article discusses modern Uzbek and Turkish women’s poetry. Also, formal researches specific to women’s poetry in sister nations were analyzed. Poems of modern Uzbek and Turkish poets Halima Ahmedova, Zulfiya Mominova Gulnoz Mominova and Turkish poets Gulten Madak, Fatma Shengul Suzar, Zaynab Arkan are studied in a comparative aspect.